WORKING ISLAMIC MANAGEMENT: SEBUAH BEST PRACTICE INTERNALISASI ISLAM DALAM ORGANISASI BISNIS KULINER - IHSAN RAHMAT; LUCKY JUWANA (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2018)
This study aims to understand Islamic management works in business organizations. We intend to expand this area of study while affirming the main argument by raising studies in culinary organizations. Waroeng Group was appointed as a case. It was considered successful in internalizing Islam into the organization's work system. Reviewing the workings of the WG along with the criteria within it are the main focus. We follow the pattern of qualitative work, such as make observations and interviews early, perform data collection, and write the results of the field to the worksheet.The study found that initial emphasis should emerge from a leader (top Management). We call it by ‘the call of the heart’, not because of the encouragement of the other party or are profitable. So understanding that leadership is a reorientation intention readable work, building work paradigm for worship (to Allah), ukhuwah Islamiyah, and worship as the income base of the organization. Then bringing up a special team that is able to present the Islamic management program. WG restructures the organization chart by providing a special position for the department of the spiritual company (DSC).The DSC is led by a person who is able to integrate and interconnection of Islam and business, call it Ustadz. Organizing the needs of employees into a DSC workload. Coaching begins with recruitment and selection, then providing sufficient time for training. WG train new employees about 40 days prior to the employment contract. Furthermore, the paradigm of working for worship has spawned a new paradigm, working for da'wah.That is a special finding in this study. The working not to save oneself, but also to insiders and outside organizations. WG provides da’wah program from internal to internal, internal to external, external to external. This study provides the way of Islamic management work, so it is considered able to answer the needs of practitioners and academics, especially Islamic management consultants to bring the Islamic culture, especially in the context of business organizations.